Changes in Education Policy in Indonesia During the Covid-19 Pandemic - Chadisa Rizky Ananda; Nuri Aslami (Penerbit Jurnal Indonesia, 2022)
This Study aims to find out about policy changes in Indonesia during the Covid-19 Pandemic. This is because the Covid 19 Pandemic is too high, which requires the goverment to make several policies regarding health and education polices that are threatened. In this study, the author use a Qualitative research method, by collecting some data or information as a tool in research .interviews and observations are considered effective which will produce data or information that is more critical. Logical, and in accordance with the facts on the ground.